Geographical indications systems, a debate in transformation. Reflections from emerging wine regions and countries - Salas Quesada, Maria del Carmen (Universidad Pedagógica y Tecnológica de Colombia, 2024)
In wine agribusiness, collective representations such as geographical indication systems are created to protect quality and differentiate each producing region in the national and international markets. The diversity of the global wine scene, new consumer demands, and socio-environmental changes are inviting us to rethink this quality protection system and enrich the debate concerning possible alternatives. This work explores the opinions about this debate from emerging wine regions and countries such as Sonora in Mexico. These spaces are in a growth, experimentation, and development phase that allows us to analyse how the possibility of adopting and regulating geographical protection models is perceived and the challenges associated with this classification and valorisation strategy. Likewise, at a broader level, this analysis seeks to reflect on the creation of alternative ways to differentiate and collectively represent the quality and value associated with the place of origin of wine production. Finally, the above aims to contribute to a better understanding of the changes faced by the diversification and transformation of the current wine industry in Latin America and globally.